LEGENDARY NARRATIVE OF KING VIKRAMADITYA: AN ARCHETYPE FOR SPIRITUAL TRANSFORMATION - Dr Shreeja Tripathi Sharma (International Journal of Innovations in Engineering Research and Technology, 2023)
The immortal memory of the legendary king Vikramaditya is not merely a eulogised ideal belonging to the past, but is rather a potential living reality which inspires generations even now. A substantial expanse of Indian folk literature continues to rekindle our consciousness with the ephemeral memory of king Vikramaditya. The mythic narrative concerning legendary king Vikramaditya contains archetypal data, which can aid in restructuring a better world view for contemporary socio-cultural order based on spiritual reinforcement.